A Monolithic Hybrid Cellulose-2.5-Acetate/Polymer Bioreactor for Biocatalysis under Continuous Liquid-Liquid Conditions Using a Supported Ionic Liquid Phase - Sandig, Bernhard; Michalek, Lukas; Vlahovic, Sandra; Antonovici, Mihaela; Hauer, Bernhard; Buchmeiser, Michael R. (Chemistry - A European Journal, 2015)
Mesoporous monolithic hybrid cellulose-2.5-acetate (CA)/polymer supports were prepared under solvent-induced phase separation conditions using cellulose-2.5-acetate microbeads 8-14μm in diameter, 1,1,1-tris(hydroxymethyl)propane and 4,4′-methylenebis(phenylisocyanate) as monomers as well as THF and n-heptane as porogenic solvents. 4-(Dimethylamino)pyridine and dibutyltin dilaurate (DBTDL), respectively, were used as catalysts. Monolithic hybrid supports were used in transesterification reactions of vinyl butyrate with 1-butanol under continuous, supported ionic liquid-liquid conditions with Candida antarctica lipaseB (CALB) and octylmethylimidazolium tetrafluoroborate ([OMIM + ][BF 4 - ]) immobilized within the CA beads inside the polymeric monolithic framework and methyl tert-butyl ether (MTBE) as the continuous phase. The new hybrid bioreactors were successfully used in dimensions up to 2×30cm (V=94mL). Under continuous biphasic liquid-liquid conditions a constant conversion up to 96% was achieved over a period of 18days, resulting in a productivity of 58μmolmg -1 (CALB)min -1 . This translates into an unprecedented turnover number (TON) of 3.9×10 7 within two weeks, which is much higher than the one obtained under standard biphasic conditions using [OMIM + ][BF 4 - ]/MTBE (TON=2.7×10 6 ). The continuous liquid-liquid setup based on a hybrid reactor presented here is strongly believed to be applicable to many other enzyme-catalyzed reactions.